Relapse of indurative tuberculosis of the skin of the lower extremities against the background of undiagnosed spontaneously cured pulmonary tuberculosis - Białoszycka, Żanna; Białoszycka , Monika; Pachevska , Alisa (Journal of Education, Health and Sport, 2025)
Introduction. In recent years, there has been a marked increase in the prevalence of cutaneous tuberculosis in Ukraine. Tuberculous lesions of the skin, as a rule, are secondary. Case description. Tuberculous lesions of the skin are typically secondary in nature. Patient N, aged 58 years, presented with a dermatological complaint on the lower extremities, characterised by pruritus, burning and functional impairment. He had been experiencing symptoms for approximately three years prior to seeking medical attention at his place of residence, where a diagnosis was not established. The dermal lesions present as dense, rounded nodules up to 1.0 cm in diameter on the lower limbs. The skin in the vicinity of the nodes displays a reddish hue with a bluish tinge. Irregularly shaped foci of cicatricial atrophy are present on the skin of the ankle-foot joints. An additional rounded formation is identified on the X-ray of the thoracic organs and lungs, taken in both direct and left lateral projections. The pathohistological examination revealed uneven infiltration in the surface layers of the dermis, comprising lymphocytes, plasma cells, and multinucleated Langhans cells, which formed non-caseous granulomas. Additionally, the dermis exhibited focal sclerosis, granulomatous vasculitis with damage to the walls of small and medium-sized vessels, and signs of lobular panniculitis. Discussion. In consideration of the patient’s complaints, anamnesis data, data from objective and special research methods, a diagnosis was formulated. A relapse of indurative tuberculosis of the skin of the lower extremities was observed. The patient presented with residual changes in a previously treated case of pulmonary tuberculosis. Conclusions. In order to facilitate an early diagnosis of tuberculosis of the skin, it is necessary to perform a mandatory X-ray examination of the organs of the chest cavity and a histological examination of the affected area of the skin at the initial visit.